When companies fund continuing training for professional recognition : what is the significance of regulation and adherence to a collective wage agreement? - Erbe, Jessica [Verfasser] (My University, 2026)
"To use their qualification to work in Germany, skilled workers trained abroad frequently need to undergo continuing training as part of the recognition process. This is particularly the case if an equivalence assessment procedure makes this a prerequisite for full recognition. This article takes data from the BIBB Training Panel to investigate how and to which extent companies support their employees in this and to examine which reasons speak against it." (BIBB-Doku)
Keywords: I 1.2 Anrechnung im Ausland erworbener Leistungen & Abschlüsse; S 3.2 Unternehmen und Behörden; 370; Auslandsqualifikation; Anerkennung; Betrieb; Weiterbildungsförderung; Weiterbildungsverhalten; BIBB-Qualifizierungspanel